Endodontic Management of Maxillary Second Molar Tooth with a Single Root and Single Canal - Neelam Mittal; Vijay Parashar; Prasad Suresh Patel (Case Reports in Dentistry)
Comprehensive understanding of variations in the root canal morphology of a maxillary molar is useful for performing successful endodontic treatment in such cases. This case report describes endodontic management of a case with such aberrant root canal morphology of a maxillary second molar having a single root and single canal.